Cellular Signaling and Anti-Apoptotic Effects of Prolactin-Releasing Peptide and Its Analog on SH-SY5Y Cells - Zmeškalová, Anna; Popelová, Andrea; Exnerová, Aneta; Železná, Blanka; Kuneš, Jaroslav; Maletínská, Lenka (International journal of molecular sciences, 2020)
Prolactin-releasing peptide (PrRP), a natural ligand for the GPR10 receptor, is a neuropeptide with anorexigenic and antidiabetic properties. Due to its role in the regulation of food intake, PrRP is a potential drug for obesity treatment and associated type 2 diabetes mellitus (T2DM). Recently, the neuroprotective effects of lipidized PrRP analogs have been proven. In this study, we focused on the molecular mechanisms of action of natural PrRP31 and its lipidized analog palm11-PrRP31 in the human neuroblastoma cell line SH-SY5Y to describe their cellular signaling and possible anti-apoptotic properties. PrRP31 significantly upregulated the phosphoinositide-3 kinase-protein kinase B/Akt (PI3K-PKB/Akt) and extracellular signal-regulated kinase/cAMP response element-binding protein (ERK-CREB) signaling pathways that promote metabolic cell survival and growth. In addition, we proved via protein kinase inhibitors that activation of signaling pathways is mediated specifically by PrRP31 and its palmitoylated analog. Furthermore, the potential neuroprotective properties were studied through activation of anti-apoptotic pathways of PrRP31 and palm11-PrRP31 using the SH-SY5Y cell line and rat primary neuronal culture stressed with toxic methylglyoxal (MG). The results indicate increased viability of the cells treated with PrRP and palm11-PrRP31 and a reduced degree of apoptosis induced by MG, suggesting their potential use in the treatment of neurological disorders.
Keywords: neuroprotektivní látky; hormon uvolňující prolaktin; methylglyoxal; Tumor Cells, Cultured; cellular signaling; Neuroblastoma; Neuropeptides; neuroprotection; Humans; neuropeptidy; Prolactin-Releasing Hormone; SH-SY5Y; primary neuronal culture; Neuroprotective Agents; Apoptosis Regulatory Proteins; inhibitors; nádorové buňky kultivované; apoptóza; proteiny regulující apoptózu; neuroblastom; lidé; Signal Transduction; prolactin-releasing peptide; Apoptosis; signální transdukce